BUILDING RESILIENCE: A HOLISTIC APPROACH MAPPRING RISKS IN PORT TERMINALS - Attila Akac; Afroditi Anagnostopoulou (International Journal for Quality Research)
The primary goal of the contemporary port industry is to mitigate risks arising from the dynamic competitive landscape. To achieve this, a range of decision-analysis tools, encompassing qualitative and quantitative methods, have been devised based on a comprehensive hazard classification system for global applicability. While numerous strategic, tactical, and operational approaches have been suggested for diverse port infrastructures, only a limited number of studies have presented a strategic framework for an integrated risk assessment plan. This research study aims to develop a holistic framework for assessing risks in port terminals from a strategic standpoint. The proposed framework explores the interconnection between risk categories and existing risk management methodologies, serving as a comparative tool for strategic decision-making processes.